Ocena historyków i historiografii w Historia Augusta (w żywotach przypisywanych Flaviusowi Vopiscusowi) - Suski, Robert (Wieki Stare i Nowe, 2019)
Heretofore little importance was attached to considerations connected with ancient historians presented in Historia Augusta, in the biographies bear the name of Flavius Vopiscus of Syracuse. However, these brief texts perhaps may enable us to understand the reason for which the author concealed his name by using six pseudonyms, and they account for the way in which he approached work with the sources. In the principal biographies of the Antonines and the Severi he drew from the imperial biographies by Marius Maximus whose work was positively evaluated in his considerations. The work contained information which was of paramount importance for the imperial biography such as the origin of the ruler or a description of his character. In the subsequent part of the Historia Augusta its creator used other sources which represented such literary genres as history and breviaria. We may infer from Scriptor’s methodological considerations that he held these literary genres in low estimation; he did not mention even one author of these sources. This supposedly influenced his polemical attitude to these source materials and the way in which he used them — he frequently interspersed their narrations with themes drawn from the works of other historians.